The Lived Experiences of Single Mothers After Childbirth: Postpartum Depression (PPD) Stories - John Paul Reloj (Diversitas Journal, 2024)
This qualitative study used Interpretative Phenomenological Analysis to analyze single mothers' postpartum depression experiences. The study highlighted the problems participants faced as students and single mothers. Satellite campus students participated in the study. The researcher used purposive and snowball sampling to identify 15 teenage single mothers with one to three children. They weren't necessarily diagnosed or treated for PPD. Single mothers experience different postpartum depression symptoms. Insecurity, tearfulness, irritability, physical symptoms, self-blame, self-harm, unreasonableness, giving up, isolation, and suicidal ideations are symptoms experienced during postpartum depression. According to their stories, PPD symptoms could be a result of the abrupt changes in their life as new mothers. Emotion-focused coping, problem-focused coping, and religious coping were most commonly used by single mothers. Future research should investigate these coping methods. This study contributes a theoretical understanding of the postpartum depression experiences and coping mechanisms of single mothers.